Which financial stocks did short sellers target in the subprime crisis? - Iftekhar Hasan; Nadia Massoud; Anthony Saunders; Keke Song (Bank of Finland, 2015)
Tracing the SEC ban on the short selling of financial stocks in September 2008, this paper investigates whether such selling activity before the 2008 short ban reflected financial companies' risk exposures in the subprime crisis. The evidence suggests that short sellers sold short stocks that had the greatest asset and insolvency risk exposures, and that the short selling of financial firms' stocks was not significantly greater than that of non-financial firms. When the short ban was in effect, the market quality of financial stocks without subprime asset exposure had deteriorated to a larger degree than that of financial companies with subprime asset exposure. The findings imply that such a regulation may mute the market disciplining effects of investors and may also serve as a counterweight to any perceived macro or systemic risk reduction benefits resulting from such a ban.
URN:NBN:fi:bof-201502131047
Keywords: G01; G14; G18; G28; G33; 330; short selling; subprime assets; financial crisis; short-sale ban; CDS spread